Wage inequality within and between firms: Macroeconomic and institutional drivers in Europe - Wouter Zwysen (European Trade Union Institute (ETUI), 2022)
Rising wage inequality is disproportionately driven by widening differences in pay between firms. This can reflect that firms' workforces are increasingly homogenous but also that the pay of similar workers increasingly differs depending on firm productivity and the way that is shared with the work-force. This paper uses cross-nationally representative European data from the Structure of Earnings Survey to study the trends in earnings and wage inequality over time between and within firms, linking these to changes in macroeconomic and institutional factors. Earnings have converged between countries within Europe, hiding increasing inequality within countries, primarily driven by differences between firms. A substantial part of increased inequality is due to variation in working time and contracts. The remainder reflects both more sorting of workers into firms with other similar workers and a divergence in the premium firms pay. European economies face some common trends brought about by macroeconomic changes such as globalisation and digitalisation. Even in the light of these major trends, differences in wage inequality within and between firms seem mainly to reflect institutional changes, particularly the changing coverage of pay agreements and union strength which shape inequality within and between firms differently, as well as the presence and bite of minimum wages. While digitalisation and globalisation play a role in raising differences between firms, institutional factors seem to have a more substantial impact on the evolution of inequality within and between firms.
Keywords: 330